Citric Acid Loaded Hydrogel-Coated Stent for Dissolving Pancreatic Duct Calculi - Jing Li; Yanwei Lv; Zheng Chen; Jiulong Zhao; Shige Wang (2024)
In recent years, the incidence of chronic pancreatitis has increased significantly. Pancreatic calculi obstruct the pancreatic duct and induce abdominal pain in the patients. Pancreatic duct stenting is the major treatment option for chronic pancreatitis with calculi. In this study, a new kind of drug-eluting stent, a pancreatic stent coated by methacrylated gelatin (GelMA) hydrogel loaded with citric acid (CA), was designed for the interventional treatment of pancreatic duct calculi. The CA loading capacity reached up to 0.7 g CA/g hydrogel-coated stent. The GelMA hydrogel coating has higher mechanical strength and lower swelling performance after loading with CA. The in vitro experiments of stents exhibited good performance in CA sustained release and the calculi can be dissolved in almost 3 days. The stents also showed good blood compatibility and cell compatibility. This research has important clinical value in the treatment of chronic pancreatitis with pancreatic calculi.